Wind resource assessment of Cuba in future climate scenarios. Issue 3 (June 2019) - Alonso Díaz, Yoandy; Bezanilla, Arnoldo; Roque, Alfredo; Centella, Abel; Borrajero, Israel; Martinez, Yosvany
The future climatic behavior of the wind resource in Cuba has not been studied in the past. This study presents a preliminary analysis of the behavior of wind speed using the regional climate model PRECIS (Providing Regional Climates for Impacts Studies) in high-resolution scenarios of climate change SRES A1B (Special Report on Emissions Scenarios), driven with boundary conditions from the General Circulation Model ECHAM5 (European Centre/HAMburg climate model) and 6 of the 16 members of the set of perturbed physics HadCM3 (Hadley Center Coupled Model, version 3) global climate model. Changes in the distribution of wind speed for three periods of 30 years in the future—2011–2040, 2041–2070, and 2071–2099—are analyzed. The PRECIS model was also run with reanalysis data during the period of 1 January 1989 to 31 December 2002. It was found that changes in wind speed will be larger in the eastern and northern coast, becoming statistically significant for the second half of this century with an increase in wind magnitude between 0.1 and 0.4 m s −1 . These areas of increased wind power match with the current projection of the Cuban wind program where the construction of 13 new wind farms are contemplated. Finally, this increase is added to the wind speed outputs of the numerical wind atlas of Cuba to estimate the values of wind speed over the three future periods.